PERAN TOKOH LINTAS AGAMA DALAM MENANGKAL GERAKAN RADIKALISME AGAMA DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi Pada Komunitas Tokoh Lintas Agama Di Kota Surakarta, Jawa Tengah) - Prasetyo, Laurentius Yananto Andi (Jurnal Ketahanan Nasional, 2013)
This paper explained the interreligious figureâs role to prevented religious radicalism. Religious radicalism had become a nonstop topic for more than a decade since the 1998 reform era. The flaring radical action in Surakarta was a threatâs form of radicalism movement. The qualitative data showed there was global politic constellation factor, indifference factor, and ideological factor, economic and psychological factor. Two dominant factors of those five factors were ideological and indifference factor. There was also role model strategy of the interreligious figure. Implication of the role was the establishment of the interreligious communication net, providing knowledge modal and the skill for the community especially in the area subject of confl ict and the establishment of good relation of all the related elements.Keywords: Leader of Cross Religions, Movement of Radicalism, Regional Resilience.